Soil Erosion as a Driver of Eutrophication An Analysis of European Lakes Using Sentinel-2 Satellite Data - Gupta, Surya (Global change biology, 2025)
© 2025 The Author(s). Global Change Biology published by John Wiley & Sons Ltd.